Cryo-Electron Microscopy of Arabidopsis thaliana Phytochrome A in Its Pr State Reveals Head-to-Head Homodimeric Architecture - Wahlgren, Weixiao Yuan; Golonka, David; Westenhoff, Sebastian; Möglich, Andreas (Frontiers in Plant Science, 2021)
Phytochrome photoreceptors regulate vital adaptations of plant development, growth, and physiology depending on the ratio of red and far-red light. The light-triggered Z/E isomerization of a covalently bound bilin chromophore underlies phytochrome photoconversion between the red-absorbing Pr and far-red-absorbing Pfr states. Compared to bacterial phytochromes, the molecular mechanisms of signal propagation to the C-terminal module and its regulation are little understood in plant phytochromes, not least owing to a dearth of structural information. To address this deficit, we studied the Arabidopsis thaliana phytochrome A (AtPhyA) at full length by cryo-electron microscopy (cryo-EM). Following heterologous expression in Escherichia coli, we optimized the solvent conditions to overcome protein aggregation and thus obtained photochemically active, near-homogenous AtPhyA. We prepared grids for cryo-EM analysis of AtPhyA in its Pr state and conducted single-particle analysis. The resulting two-dimensional class averages and the three-dimensional electron density map at 17 Å showed a homodimeric head-to-head assembly of AtPhyA. Docking of domain structures into the electron density revealed a separation of the AtPhyA homodimer at the junction of its photosensor and effector modules, as reflected in a large void in the middle of map. The overall architecture of AtPhyA resembled that of bacterial phytochromes, thus hinting at commonalities in signal transduction and mechanism between these receptors. Our study paves the way towards future studies of the structure, light response and interactions of full-length phytochromes by cryo-EM.